Cycling Frequency Changes During the COVID-19 Pandemic in Canada’s Most Populous Urban Regions - Remington Latanville; Raktim Mitra; Meghan Winters; Paul Hess; Kevin Manaugh (Findings)
We surveyed 2,066 residents of Toronto and Montréal and Vancouver-area municipalities to identify changes in self-reported cycling frequency from before to during the COVID-19 pandemic. Results indicate that 5% of people who were infrequent cyclists (less than once a week) became frequent cyclists (at least once a week) over the pandemic; these were more likely to be men, those aged 30-59 years, those living in more urban neighbourhoods, and those who felt that new cycling facilities provided better access to their usual and/or desired locations via active transportation.